Kinetics Degradation and Shelf Life of Curcumin from Turmeric (Curcuma domestica Val) with Ethanol Extract Coated by Maltodextrin at Room Temperature Storage - Jaya Hardi; Ruslan Lina (Universitas Negeri Medan, 2023)
Curcumin extract from the turmeric plant is unstable to light, temperature, and changes in pH, therefore it is necessary to be coated with biopolymers to have a longer shelf life. This study aims to determine the type of degradation kinetics of maltodextrin-coated curcumin and its shelf life at room temperature storage. Encapsulation was performed using an emulsion technique combined with freeze drying with a ratio of turmeric ethanol extract to maltodextrin of 7: 5 (w/w). The results showed that the efficiency of coating the ethanol extract of turmeric with maltodextrin was 31.26%. Kinetics degradation of curcumin coated with maltodextrin follows zero-order reaction kinetics. The microcapsule of turmeric ethanol extract coated with maltodextrin has a shelf life at room temperature of 8.35 weeks.